Complex rehabilitation of children with CCLP after adverse postoperative outcomes - Mirzaeva Firuza Avazovna; Yadgarova Gulnora Sadritdinovna (Zien Journals, 2022)
The study and improvement of the life status of children with congenital cleft lip and palate using temporary silicone nipples and plates showed a positive effect on the development of speech defects and on the anthropometric parameters of the maxillae and dentoalveolar arch. 135 infants born with CCLP were recruited, of which 83 were male and 52 were female. The babies were divided into 2 groups. Group 1 - the main group of 68 infants (of which 42 are male and 26 are female) and group 2 - the control group of 66 infants (of which 41 are male and 26 are female). The studied changes and their systematization lead to a decrease in maxillofacial pathologies, as well as growth and development of the definition, which contributes to the non-hormonal development of the child. The introduction of the obtained data into practical healthcare will reduce the proportion of maxillofacial anomalies. For the first time, the method of using early orthodontic treatment of children with CCLP, carried out with the help of the "Dental Obturator for orthodontic treatment of children with CCLP" was scientifically substantiated
Keywords: cleft; children; palate; silicone